Dualisme Pengelolaan Pendidikan Tinggi dalam Perspektif Keadilan Konstitusional - Yohanes Brilian Jemadur (Jurnal Hukum Lex Generalis, 2025)
Education is a constitutional right of citizens guaranteed by the 1945 Constitution of the Republic of Indonesia, particularly Article 31 which affirms the state's obligation to provide a national education system. This provision is further elaborated in Law Number 20 of 2003 on the National Education System, which positions education as an integrated system in its implementation. Furthermore, the regulation of higher education is specifically governed by Law Number 12 of 2012 on Higher Education. However, in institutional practice, the administration of higher education in Indonesia demonstrates a dualistic management structure between general higher education institutions under the ministry responsible for education and religious higher education institutions under the ministry responsible for religious affairs. This condition raises juridical issues regarding the consistency of the national education system and its implications for the principle of constitutional justice in the fulfillment of the right to education. This study aims to analyze the regulation of the dualism in the management of higher education within the Indonesian legal system and to assess its implications for the principle of constitutional justice in the national education system. This research employs a normative legal research method using statutory and conceptual approaches. Legal materials were obtained through library research on legislation, books and relevant academic journals, which were then analyzed qualitatively using normative analysis. The results of this study indicate that the dualism in the management of higher education potentially leads to institutional fragmentation, regulatory disharmony and policy inconsistency in higher education governance, which may affect the integration of the national education system. Such conditions have implications for the consistency in the implementation of the principle of constitutional justice in the administration of higher education. Therefore, strengthening policy integration and harmonizing higher education regulations are necessary to ensure that the administration of education is more consistent, equitable and aligned with the constitutional mandate.